Peningkatan Keaktifan Belajar IPA Melalui Model Pembelajaran Inkuiri pada Siswa Kelas VI SD Negeri Niki-Niki IV - Margarida Arista Susanti De Araujo (Jurnal Insan Pendidikan dan Sosial Humaniora, 2026)
This classroom action research aimed to improve students' learning activeness in Science through the implementation of the Inquiry Learning Model in Grade VI students of SD Negeri Niki-Niki IV. The study was conducted in two cycles involving 18 students consisting of 8 male and 10 female students. Data were collected through observation, interviews, documentation, and learning outcome tests. Data analysis employed descriptive quantitative and qualitative techniques. The results indicated that the implementation of the inquiry learning model successfully increased students' learning activeness. In Cycle I, the average learning activeness reached 55.7%, while in Cycle II it increased to 67.4%. Students demonstrated greater participation in classroom discussions, increased confidence in expressing opinions, and better responsibility in completing learning tasks. The findings suggest that the inquiry learning model creates a more active and student-centered learning environment. Therefore, the inquiry learning model can be considered an effective alternative strategy for improving students' learning activeness in science learning at the elementary school level.